Sistem Deklararatif Hak Cipta terhadap Suatu Gambar Sketsa yang Di-Upload di Instagram - Muhammad Fakhrihassan; Budi Agus Riswandi (Fakultas Hukum Universitas Islam Indonesia, 2025)
Although technological development provides open to various types of content on social media, it leads to a tendency among society to overlook the integrity of a creator's copyrighted works. Consequently, copyright protection in the digital era aims not only to safeguard the interests of creators but also to maintain respect for creativity and innovation. This study seeks to analyze the application and legal implications of the declarative system as a form of automatic copyright protection for sketches uploaded to Instagram. The research questions focus on how the declarative system offers protection and how this affects the creator’s legal position. The combination of normative legal research methods with statutory and analytical approaches not only assists in answering the research questions but also opens new perspectives regarding copyright application in a digital context. The findings reveal that the act of announcement is not the sole obligation required to obtain automatic protection for works. Declarative protection is inherent from the moment a sketch is realized in a tangible form. Uploading the sketch produces legal implications by establishing exclusive rights for the creator that must be respected by others, along with the responsibility of electronic system providers to ensure a conducive environment for users.